METODE ELEKTROFOTOKATALISIS DAN FOTOKATALISIS DENGAN TiO2 PADA DEKOLORISASI REMAZOL GOLDEN YELLOW RNL DAN PENURUNAN KONSENTRASI ION LOGAM Cd2+ SECARA SIMULTAN - N.R., Ade Novianti; , M.Si., Drs. Gunawan; Haris, M.Si., Drs. Abdul (Chem Info Journal, 2013)
Experiments on elektrofotokatalisis using TiO2 on decolorization remazol golden yellow RNL and decreased concentrations of Cd2+ metal ion simultaneously have performed. The purpose of this study was to compare the effectiveness of photocatalytic TiO2 in the form of thin layers of powder that was used to electrophotocatalyzed remazol golden yellow RNL and to reduce the concentration of metal ion of Cd2+. The electrophotokatalysis method use TiO2/FTO working electrode and photocatalytic TiO2 powder for 240 minutes. UV-Vis spectrophotometer was used to determine the absorbance decrease of remazol golden yellow RNL, while atomic absorption spectrophotometer (AAS) was used to determine the decrease concentration of metal ion Cd2+. The results obtained in this study for working electrode TiO2/FTO are more effective to decolorize remazol golden yellow RNL and to decrease the concentration of metal ion Cd2+ compared to the use of TiO2 powder. Electrophotokatalysis using TiO2/FTO working electrode was capable to decolorize remazol golden yellow RNL by 87.9% and to lower the concentration of metal ion of Cd2+ by 82.7%, while the photocatalytic method was only able to decolirize remazol golden yellow RNL by 25.87% and to decrease the concentration of metal ion Cd2+ amounted to 53.2%Â Â Â